THE ROLE OF INTERCULTURAL COMPETENCE IN ENGLISH LANGUAGE TEACHING - Khoiriya Latifah; Doston Pirnazarov; Tagayeva Umida; Ro’ziyeva Umida; Axmedova Dilora (Web of Journals Publishing, 2025)
In the context of globalization, intercultural competence has emerged as an essential element of effective English language teaching. As learners engage with English not merely as a linguistic system but as a vehicle of cross-cultural communication, teachers must adopt approaches that integrate cultural awareness and sensitivity. This article explores the theoretical foundations, pedagogical implications, and practical applications of intercultural competence in ELT, supported by empirical studies, classroom examples, and critical insights.
Keywords: Intercultural Communicative Competence (ICC), English as an International Language (EIL), Global Englishes, Cultural Awareness, Critical Pedagogy in ELT, Sociocultural Approach to Language Teaching, Symbolic Competence, Byram’s Model of ICC, Learner Identity in ELT, Contextualized Language Education, Reflective Teaching Practices, Comparative Cultural Education, Cross-Cultural Pragmatics, Uzbek ELT Research, Intercultural Dialogue in Language Classrooms.